The effects of composition, diameter and post-curing methods on the flexural properties of fiber posts. - Nadia Ereifej; Eugenio Garcia; Diego Noroña; Rosa Grande (Universidad de Concepción., 2016)
Objective: This study evaluated the influence of fiber composition, diameter and post-curing treatments performed at relining on flexural strength and modulus of fiber-posts. Materials and methods: Sixty posts of Reforpost® Glass Fiber [GF]) and Reforpost® Carbon Fiber [CF] (Angelus, Londrina, PR, Brazil) with diameters of 1.0mm and 1.4mm were used. Each group was further subdivided into three subgroups (n=5) according to treatment received: dry-stored control group (C), oven-cured (Ov) or autoclaved (Ac). A universal testing machine measured flexural strength and modulus of all specimens. Results: Post composition and post-curing treatments had no significant effects on flexural properties of specimens while post diameter had significant effects (p<0.05). The highest flexural strength and modulus (MPa) (1331±95.8 and 21532±1550, respectively) were obtained with Ov/GF/1.1, while lowest values (890±79.4 and 10675±952, respectively) were for Ac/GF/1.5. Conclusions: 1.1mm diameter posts had better mechanical properties than 1.5mm thick posts. Neither post composition nor post-curing procedures affected the mechanical properties of relined posts.